2012
DOI: 10.1186/1472-6963-12-267
|View full text |Cite
|
Sign up to set email alerts
|

The variation of acute treatment costs of trauma in high-income countries

Abstract: BackgroundIn order to assist health service planning, understanding factors that influence higher trauma treatment costs is essential. The majority of trauma costing research reports the cost of trauma from the perspective of the receiving hospital. There has been no comprehensive synthesis and little assessment of the drivers of cost variation, such as country, trauma, subgroups and methods. The aim of this review is to provide a synthesis of research reporting the trauma treatment costs and factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
1
19
1
Order By: Relevance
“…Average per patient costs for severely injured patients in this study were less than those reported internationally 7 and locally. 28 In comparing costs, it is necessary to collect data across multiple sites so that discrepancies caused by variations in efficiency across centres are offset.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Average per patient costs for severely injured patients in this study were less than those reported internationally 7 and locally. 28 In comparing costs, it is necessary to collect data across multiple sites so that discrepancies caused by variations in efficiency across centres are offset.…”
Section: Discussioncontrasting
confidence: 40%
“…6 Trauma treatment represents a significant cost to the community and different funding models are used to resource the healthcare sector with varying degrees of accuracy. 7,8 In NSW, an episode-based funding model (also known as casemix-based funding) has been adopted for acute healthcare services 9 where a healthcare facility is allocated a predetermined financial payment for each type of patient episode, defined by an Australian Refined Diagnosis-Related Group (AR-DRG). 10 For some health conditions, such as rehabilitation or palliative care, episode funding models and AR-DRG have not been found to be good indicators of the 'true' types of patient episodes.…”
mentioning
confidence: 99%
“…During the study period, a HEMS pre-hospital and inter-hospital patient cost, on average, ~$25,000 and ~$42,000 respectively to treat, although considerable variation existed between patients, which has also been demonstrated previously [27]. Our results show HEMS patients are potentially underfunded in the order of ~$2,500 - ~$2,900 per patient transported pre-hospital and inter-hospital respectively.…”
Section: Discussionsupporting
confidence: 80%
“…probably due to a different pattern in productivity costs among age categories. Other variables such as high ISS, specific body regions (abdomen, spine and brain injury) and LOS were also identified as prognostic factors for medical costs in a review [38].…”
Section: Plos Onementioning
confidence: 99%